The Local Wisdom of Angkola in Efforts to Love the Environment - Yusni Khairul Amri; Diani Syahputri (Budapest International Research and Critics University, 2020)
Damage to the natural environment is a reflection of the disruption of the earth's lungs (forests) as a result of anthropocentric attitudes of humans who exploit excessively. To balance the natural environment so that it is not increasingly damaged, which is to foster human behavior or ethics that care about the environment. This study is entitled Angkola LocalWisdom in Efforts to Love the Environment. The problem to be explored is the Angkola traditional ceremony containing wisdom values in an effort to love the environment. As well as giving a general description of how the role of the Angkola traditional leaders through traditional ceremonies so that the local wisdom of the Angkola custom is known in an effort to love the environment. The method used is a qualitative method with anthropological and phenomenological approaches. The results of this study are: a) The introduction of the plant lexicon early on, b) The use of the plant lexicon as a philosophical character according to the plant lexicon, c) The local wisdom of Angkola's custom in the effort to love the environment is an education of cultural characteristics through the plant lexicon used in the plant lexicon custom.